Severe refractory idiopathic warm autoimmune haemolytic anaemia responsive to complement inhibition with eculizumab. Issue 1 (13th December 2018) - Neave, Lucy; Wilson, Andrew J; Lissack, Maxine; Scully, Marie
Abstract : We report a case of severe idiopathic warm autoimmune haemolytic anaemia (wAIHA) which was initially poorly responsive to treatment with corticosteroids, intravenous immunoglobulin, mycophenolate mofetil and rituximab, and required transfusion of more than 30 units of red cells over 12 weeks. Off-label use of the terminal complement pathway inhibitor, eculizumab, led to rapid amelioration of the haemolysis, presumably by the inhibition of an intravascular component, and allowed time for slower acting immunosuppressive agent to take effect. This novel approach warrants further evaluation, given the poor prognosis of multirefractory wAIHA.